Current viewpoints on DSM‐5 in Japan. Issue 9 (31st August 2016) - Kuroki, Toshihide; Ishitobi, Makoto; Kamio, Yoko; Sugihara, Genichi; Murai, Toshiya; Motomura, Keisuke; Ogasawara, Kazuyoshi; Kimura, Hiroyuki; Aleksic, Branko; Ozaki, Norio; Nakao, Tomohiro; Yamada, Kazuo; et al.
Abstract : The fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM‐5) was published in 2013, and its official Japanese version was published in 2014. The Japanese Government uses classifications from the 10th revision of the I nternational C lassification of D iseases (ICD‐10) to categorize disorders and determine treatment fees. However, since the publication of the DSM‐III, the use of the DSM system has become prevalent in research and educational settings in Japan. In addition to traditional psychiatry, both the ICD and the DSM are taught by many Japanese medical schools, and virtually all clinical research and trials refer to the DSM to define targeted disorders. Amid the current backdrop in which the reputation of the DSM‐5 is being established, the editorial board of P sychiatry and C linical N eurosciences has asked Japanese experts across 12 specialties to examine the structure of the DSM‐5, including the following categories: Neurodevelopmental Disorders, Schizophrenia Spectrum Disorders, Major Depression, Bipolar Disorders, Obsessive–Compulsive Disorders, Somatic Symptom Disorder, Eating Disorders, Substance‐Related and Addictive Disorders, Gender Dysphoria, and Neurocognitive Disorders. Although opinions were only obtained from these selected experts, we believe that we have succeeded, to a certain extent, in presenting views that are representative of each specialty.